Wrestling with God in Context : Revisiting the Theology and Social Vision of Shoki Coe - Joseph, M. P.; Huang, Po Ho; Hsu, Victor (Fortress Press, 2018)
Shoki Coe was among the first to speak of ""contextualization"" in theology. Yet he remains little known outside his native Taiwan. This book introduces Coe and evaluates his contributions to missiology and ecclesiology. Coe shaped a generation of reflection on God, culture, and history. The chapters in this volume tackle the critical, methodological issues related to doing theology, reading the Scriptures, and being the church.